Rejecting abyssal thinking in the language and education of racialized bilinguals: A manifesto - García, Ofelia; Flores, Nelson; Seltzer, Kate; Wei, Li; Otheguy, Ricardo; Rosa, Jonathan (Critical inquiry in language studies, 2021)
Following Boaventura de Sousa Santos, the authors of this article reject the type of "abyssal thinking" that erases the existence of counter-hegemonic knowledges and lifeways, adopting instead the "from the inside out" perspective that is required for thinking constructively about the language and education of racialized bilinguals. On the basis of deep personal experience and extensive field-work research, we challenge prevailing assumptions about language, bilingualism, and education that are based on raciolinguistic ideologies with roots in colonialism. Adopting a translanguaging perspective that rejects rigid colonial boundaries of named languages, we argue that racialized bilingual learners, like all students, draw from linguistic-semiotic, cultural, and historical repertoires. The decolonial approach that guides our work reveals these students making a world by means of cultural and linguistic practices derived from their own knowledge systems. We propose that in order to attain justice and success, a decolonial education must center non-hegemonic modes of "otherwise thinking" by attending to racialized bilinguals' knowledges and abilities that have always existed yet have continually been distorted and erased through abyssal thinking.